2021
DOI: 10.1016/j.envpol.2021.117404
|View full text |Cite
|
Sign up to set email alerts
|

Early life multiple exposures and child cognitive function: A multi-centric birth cohort study in six European countries

Abstract: Epidemiological studies mostly focus on single environmental exposures. This study aims to systematically assess associations between a wide range of prenatal and childhood environmental exposures and cognition. The study sample included data of 1298 mother-child pairs, children were 6–11 years-old, from six European birth cohorts. We measured 87 exposures during pregnancy and 122 cross-sectionally during childhood, including air pollution, built environment, meteorology, natural spaces, traffic, noise, chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…We have no explanation for this unexpected finding, although this is not the first time that a protective effect on children's cognitive function of an apparently harmful exposure during pregnancy has been described in the scientific literature. A multicentric birth cohort study in six European countries has associated higher prenatal mercury levels and maternal alcohol consumption, two harmful exposures, during pregnancy with better cognitive performance in children at 6-11 y [70]. Similarly, another study has shown that higher organochlorine prenatal exposure can increase attentional function (i.e., the hit reaction time) in girls at age 8 [71].…”
Section: Discussionmentioning
confidence: 99%
“…We have no explanation for this unexpected finding, although this is not the first time that a protective effect on children's cognitive function of an apparently harmful exposure during pregnancy has been described in the scientific literature. A multicentric birth cohort study in six European countries has associated higher prenatal mercury levels and maternal alcohol consumption, two harmful exposures, during pregnancy with better cognitive performance in children at 6-11 y [70]. Similarly, another study has shown that higher organochlorine prenatal exposure can increase attentional function (i.e., the hit reaction time) in girls at age 8 [71].…”
Section: Discussionmentioning
confidence: 99%
“…Trained fieldwork technicians measured three cognitive domains in children using a battery of computer-based tests: fluid intelligence (Raven Coloured Progressive Matrices Test [CPM]), attention function (Attention Network Test [ANT]) and working memory (N-Back task). Complete outcome descriptions are provided in [86]. The CPM comprised a total of 36 items and we used the total number of correct responses as the outcome.…”
Section: Methodsmentioning
confidence: 99%
“…and working memory (N-Back task). Complete outcome descriptions are provided in [86]. The CPM comprised a total of 36 items and we used the total number of correct responses as the outcome.…”
Section: Developmental Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the exposome approach may help identify determinants of unfavorable BP more scientifically and develop prevention priorities. Furthermore, such an exposome method has achieved its recent application in systematically assessing urban environmental exposures and numerous child health outcomes in Europe, , including one study that specifically focused on BP in children, which identified several relevant environmental exposures (e.g., air pollution) . However, none studies have analyzed the impact of urban environment on BP in adults using such an exposome approach.…”
Section: Introductionmentioning
confidence: 99%